Analysis Of The Effectiveness Of Work Planning In Improving The Performance Of Civil Servise Police Unit/ Satpol PP - Eka Rofiyanti; Eva Arofah; Dwi Agustina; Sukandi (Ilomata International Journal of Social Science, 2021)
Problems that occur in the effectiveness of work planning in controlling street vendors are still not maximal performance, when viewed from the factors of Effectiveness of Consequences and Impact of Outputs in achieving objectives, the level of success in achieving predetermined targets and clarity of achievement of goals. This is supported by the data obtained by the Civil Service Police Unit (Satpol PP) of Pancoran Sub-district, which have varied work planning effectiveness criteria from 2018 to 2019, from street vendors’ orderliness to realizing street vendors, which are still far from different from the target of curbing. And from 2018 to 2019 the level of effectiveness can be included in the criteria for being quite effective. This research method is a descriptive study with a qualitative approach. Qualitative descriptive research aims to describe and describe events and phenomena that occur in the field and present data in a systematic, factual, and accurate manner regarding the facts that occur in the field. Data collection was done by using observation, interview and documentation techniques. Researchers used source triangulation to check the validity of the research data. Data analysis in this study uses three components consisting of data reduction, data presentation, and conclusion. The results of the study are known (1) The effectiveness of work planning of the Civil Service Police Unit (Satpol PP) at Pancoran Sub-district in street vendors’ orderliness in improving the work performance that has been implemented in the dimensions of Effectiveness of Reach Effects, Impact of Outputs in achieving objectives, the level of success in achieving predetermined targets and clarity of achieving goals. (2) Obstacles in implementing the effectiveness of Street Vendors/PKL work planning who do not understand the regulations, there is no relocation place for street vendors and street vendors who consider public facilities a strategic business place for trading. (3) The solution for the socialization of street vendors about policy regulations is carried out by means of humane communication and new relocation sites.